2012
DOI: 10.1681/asn.2012030260
|View full text |Cite
|
Sign up to set email alerts
|

Donor ABCB1 Variant Associates with Increased Risk for Kidney Allograft Failure

Abstract: The impact of variation within genes responsible for the disposition and metabolism of calcineurin inhibitors (CNIs) on clinical outcomes in kidney transplantation is not well understood. Furthermore, the potential influence of donor, rather than recipient, genotypes on clinical endpoints is unknown. Here, we investigated the associations between donor and recipient gene variants with outcome among 4471 white, CNI-treated kidney transplant recipients. We tested for 52 single-nucleotide polymorphisms (SNPs) acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 40 publications
1
57
3
Order By: Relevance
“…This SNP has recently been studied and did not show a relationship with graft survival in a large cohort of transplant patients. 16 We did not find an association between CYP3A5 and transplant outcomes. Carriers of the CYP3A5*1/*1 variant are expressers of CYP3A5 and have higher dose requirements and lower cyclosporine trough levels in comparison with CYP3A5*3/*3 carriers.…”
Section: Demographiccontrasting
confidence: 54%
See 1 more Smart Citation
“…This SNP has recently been studied and did not show a relationship with graft survival in a large cohort of transplant patients. 16 We did not find an association between CYP3A5 and transplant outcomes. Carriers of the CYP3A5*1/*1 variant are expressers of CYP3A5 and have higher dose requirements and lower cyclosporine trough levels in comparison with CYP3A5*3/*3 carriers.…”
Section: Demographiccontrasting
confidence: 54%
“…Finally, we did not collect donor DNA. A study by Moore et al 16 has demonstrated an association with donor CC genotype at C3435T within ABCB1 and kidney allograft failure.…”
Section: Demographicmentioning
confidence: 99%
“…In a discovery cohort of 811 patients, the 3435CC donor genotype was significantly associated with an increased risk of long-term graft failure, compared with that in non-CC carriers, and this finding was validated in two independent patients cohorts (n = 675 and 2985). The reasons for this inverse result are currently unclear [101].…”
Section: Cyclosporinementioning
confidence: 99%
“…In a very large cohort (n = 4471 white kidney transplant recipients), it was the 3435CC donor genotype (not 3435TT as in the study by Ma et al) that was associated with a worse death-censored graft survival. [70] The discrepancies between these studies are unexplained. Again differences in sample size, patient characteristics, and duration of follow-up may form an explanation.…”
Section: Nephrotoxicitymentioning
confidence: 99%